2022
DOI: 10.14405/kjvr.20210046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prognostic factors in dogs with mammary gland tumors: 60 cases (2014-2020)

Abstract: Canine mammary gland tumors are the most common neoplasms in intact female dogs. Approximately half of all mammary tumors are malignant, and there is a risk of metastasis, which is associated with a poor prognosis. This study is to evaluate the prognostic factors of canine mammary gland tumors and the risk factors associated with the development of malignant tumors. From 2014 to 2020, 60 dogs with mammary gland tumors that underwent surgical treatment were evaluated in this retrospective study. Tumor size, TNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…However, the prognosis of the treatment depends on many factors the age of the dog, tumor stage and size, and neutering status. This is in agreement with the studies by Moon et al (2022) when they analyzed 60 cases of CMC to evaluate the prognosis after the tumor resection. The consensus information creates a new paradigm in the search for or improving the therapeutic modalities of CMC.…”
Section: Canine Mammary Carcinoma Treatmentsupporting
confidence: 92%
“…However, the prognosis of the treatment depends on many factors the age of the dog, tumor stage and size, and neutering status. This is in agreement with the studies by Moon et al (2022) when they analyzed 60 cases of CMC to evaluate the prognosis after the tumor resection. The consensus information creates a new paradigm in the search for or improving the therapeutic modalities of CMC.…”
Section: Canine Mammary Carcinoma Treatmentsupporting
confidence: 92%
“…This can be partially attributed to an infiltrative growth pattern or inflammatory mammary carcinoma without a defined separate palpable mass. We confirmed that the number of tumours had no effect on tumour behaviour, grade, tumour necrosis, tumour ulceration, and prognosis as each tumour may reveal different behaviour and grade 20 , 58 , 60 , 78 .…”
Section: Discussionsupporting
confidence: 70%
“…The left glands were more often affected, however, this observation should be considered incidental. We showed that the location of malignant CMTs did not affect prognosis 58 , 60 , 81 , 82 ; however, in a recent study, dogs with the affected 1 st gland had a higher recurrence rate 58 .…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations